Afghanistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper and Statistical Appendix presents a debt sustainability analysis for Afghanistan. The analysis is based on a simple spreadsheet model that calculates indicators of sustainability in terms of ratios of the net present value (NPV) of debt and debt service to relevant macroeconomic aggregates over 2005-30. Five scenarios are examined in the paper. Key vulnerability ratios are assessed under each scenario and compared with sustainability thresholds under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The results obtained are also discussed in detail in the paper.